The Himalayan Conifers V. The Succession of Forest Communities in Chir Pine (Pinus roxburghii) Forests of the Punjab and Himachal Pradesh - Mohan, N. P.; Puri, G. S. (Indian Forester, 1956)
Forest communities in the chir pine forest of the Punjab and Himachal Pradesh have been studied in detail. The three forest types of Mohan have been re-classified into six for the purpose of giving a correlation between the vegetation and soil features and to indicate successional trends. Brief description of these types is given and the trend of succession in these forest communities is described in some detail. The succession proceeds as follows :- (1) On sand rock substratum- Chir pine → Chir pine - Terminalia chebula with an undergrowth mainly of Carissa spinarum. ( 2) On deep alluvium- Chir pine → Mixed chir pine - broad leaved species of Terminalia, Lannea, Albi ia, Cedrela, Eugenia, Phyllanthus, etc. ( 3) On Himalayan schistose rocks- Chir pine → Quercus incana - Rhododendron arboreum - Pieris ovalifolia. ( 4) On moist ferruginous clayey substratum- Chir pine with Carissa or/and Dodonaea → mixed Chir pine broad leaved species. On account of intense biotic features the successional trends outlined above may be slightly altered. In some places intermediate seral stages may become feature of vegetation, at others degraded types may assume different composition, or structure. Soil profiles from the six types have also been studied and the data presented in tabular form.